Fostering Unity: Collaborative Eﬀorts for Global Harmony (Bodhi Path, 2025)
This article intends to explore the potential that Buddhist principles hold to foster global unity and harmony in the contemporary issues of political nature. The teachings offered by Buddhism contribute to the idea of world peace and global harmony. Through the concepts of such the theory of interdependence or dependent arising (pratītyasamutpāda) and compassion (karuṇā), a world that has harmony and peace can be cultivated. (Anālayo, 2020)
Keywords: Fostering Unity; Global Harmony; Buddhism